CHD1 regulates cell fate determination by activation of differentiation-induced genes. Issue 13 (5th May 2017) - Baumgart, Simon J.; Najafova, Zeynab; Hossan, Tareq; Xie, Wanhua; Nagarajan, Sankari; Kari, Vijayalakshmi; Ditzel, Nicholas; Kassem, Moustapha; Johnsen, Steven A.
Abstract: The coordinated temporal and spatial activation of gene expression is essential for proper stem cell differentiation. The Chromodomain Helicase DNA-binding protein 1 (CHD1) is a chromatin remodeler closely associated with transcription and nucleosome turnover downstream of the transcriptional start site (TSS). In this study, we show that CHD1 is required for the induction of osteoblast-specific gene expression, extracellular-matrix mineralization and ectopic bone formation in vivo . Genome-wide occupancy analyses revealed increased CHD1 occupancy around the TSS of differentiation-activated genes. Furthermore, we observed that CHD1-dependent genes are mainly induced during osteoblast differentiation and are characterized by higher levels of CHD1 occupancy around the TSS. Interestingly, CHD1 depletion resulted in increased pausing of RNA Polymerase II (RNAPII) and decreased H2A.Z occupancy close to the TSS, but not at enhancer regions. These findings reveal a novel role for CHD1 during osteoblast differentiation and provide further insights into the intricacies of epigenetic regulatory mechanisms controlling cell fate determination.